Hello :
sin(x) + cos(x) = √2(1/√2 sin(x) +1/√2 cos(x))
but : 1/√2 = cos(π/4) = sin(<span> π/4)
</span>sin(x) + cos(x) = √2( cos(π/4)sin(x) + sin( π/4) cos(x)) =√2<span>sin(x + π/4)
</span>because : cos(π/4)sin(x) + sin( π/4) cos(x)=sin(x + π/4) by identity :
sin(a+b) = sina cosb +cosa sinb
Answer:
x = 3
Step-by-step explanation:
4x+2 = x+11
Subtract x from each side
4x+2-x = x+11-x
3x+2 =11
Subtract 2 from each side
3x+2-2 =11-2
3x = 9
Divide by 3
3x/3 =9/3
x = 3
Answer:
1/2
Step-by-step explanation:
Since we have two points, we can use the slope formula
m = (y2-y1)/(x2-x1)
= (22-21)/(6-4)
= 1/2
The first one is 0,5 the second one is 1,3 last one is 2,1